PHYSICOCHEMICAL BASES OF THE REMOVAL PROCESS OF BIOCIDAL REAGENT ON BASIS OF POLYHEXAMETHYLENEGUANIDINE FROM THE WATER WITH THE USE OF WEAK ACID CATION EXCHANGE RESIN - Сусь, М. О.; Мітченко, Т. Є.; Макарова, Н. В. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2010)
The paper deals with the investigation of polyhexamethyleneguanidine (PGMG) and weak acid cation exchange resin interaction mechanism. In addition, to organize efficient posses of PHMG excess removal from the water it was very important to find out the character of different factors influence on the sorption of PHMG by chosen resin. The ion exchange mechanism of PHMG and cation exchange resin interaction was established. Besides, it has shown that efficiency of PGMG sorption depends on the resin ionic form and ionic composition of water.